Idle Expenditure on Construction and Upgradation of Two PHCs in Meghalaya - CAG of India (CAG of India)
Expenditure of ₹ 12.35 crore on construction and upgradation of two Primary Health Centres proved idle as these centres were not made operational thereby, defeating the objective to provide curative, preventive, promotive and family welfare services to the targeted population.